Osteoporosis and Fragilty Fractures: An Overview. - Ahmet Aslan (Acta Medica Alanya)
Osteoporosis (OP); It is a metabolic bone disease characterized by decreased bone mineral density (BMD) and bone strength, increased bone fragility and fracture risk, and deterioration in the microarchitecture of bone tissue. The most important cause of morbidity and mortality in OP are fragility fractures such as osteoporotic hip fractures. Prevention and treatment of osteoporosis can prevent hip fractures and comorbidities. In this paper, the available information about Osteoporosis and Osteoporotic fractures is briefly reviewed.